Differential Contribution of the Aryl-Hydrocarbon Receptor and Toll-Like Receptor Pathways to IL-8 Expression in Normal and Cystic Fibrosis Airway Epithelial Cells Exposed to Pseudomonas aeruginosa - Roussel, Lucie; LaFayette, Shantelle; Nguyen, Dao; Baglole, Carolyn J.; Rousseau, Simon (Frontiers in Cell and Developmental Biology, 2016)
Pseudomonas aeruginosa are gram-negative bacteria that frequently infect the lungs of cystic fibrosis (CF) patients. This bacterium is highly responsive to changes in its environment, resulting in the expression of a diverse array of genes that may contribute to the host inflammatory response. P. aeruginosa is well-known to induce neutrophilic inflammation via the activation of Toll-Like Receptors (TLRs). Recently, it was shown that pyocyanin, a phenazine produced by P. aeruginosa, binds to the aryl hydrocarbon receptor (AhR), leading to neutrophilic inflammation as part of the host defense response. In this study, we have investigated the contribution of the TLR and AhR signaling pathways to the expression of the neutrophil chemoattractant IL-8 in response to P. aeruginosa diffusible material. Although both pathways are involved in IL-8 synthesis, the AhR played a greater role when planktonic P. aeruginosa was grown in a media favoring phenazine synthesis. However, when P. aeruginosa was grown in a media that mimics the nutritional composition of CF sputa, both pathways contributed similarly to IL-8 synthesis. Finally, when P. aeruginosa was grown as a biofilm, the TLR pathway did not contribute to biofilm-driven IL-8 synthesis and AhR was found to only partially contribute to IL-8 synthesis, suggesting the contribution of another unknown signaling pathway. Therefore, the interaction between P. aeruginosa and airway epithelial cells is very dynamic, and sensor engagement is variable according to the adaptation of P. aeruginosa to the CF lung environment.